2019
DOI: 10.1111/ecog.04463
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral response of a mobile marine predator to environmental variables differs across ecoregions

Abstract: Animal movement and habitat selection are in part a response to landscape heterogeneity. Many studies of movement and habitat selection necessarily use environmental covariates that are readily available over large‐scales, which are assumed representative of functional habitat features such as resource availability. For widely distributed species, response to such covariates may not be consistent across ecosystems, as response to any specific covariate is driven by its biological relevance within the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…While most individuals in this study were mature, previous studies on juveniles have also reported similar habitat use patterns between open-ocean and continental shelf use (Rogers et al, 2015;Vaudo et al, 2017;Byrne et al, 2019). Juveniles tagged off the Yucatan Peninsula demonstrated high residency to the eastern edge of the Campeche Bank (Vaudo et al, 2017;Byrne et al, 2019), and juveniles tagged off the coast of Australia exhibited high site fidelity to the mid-outer continental shelf near the Great Australian Bight (Rogers et al, 2015). This shallower, continental shelf habitat is likely attractive due to the abundance and variety of prey available compared to open-ocean habitats (Byrne et al, 2019).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…While most individuals in this study were mature, previous studies on juveniles have also reported similar habitat use patterns between open-ocean and continental shelf use (Rogers et al, 2015;Vaudo et al, 2017;Byrne et al, 2019). Juveniles tagged off the Yucatan Peninsula demonstrated high residency to the eastern edge of the Campeche Bank (Vaudo et al, 2017;Byrne et al, 2019), and juveniles tagged off the coast of Australia exhibited high site fidelity to the mid-outer continental shelf near the Great Australian Bight (Rogers et al, 2015). This shallower, continental shelf habitat is likely attractive due to the abundance and variety of prey available compared to open-ocean habitats (Byrne et al, 2019).…”
Section: Discussionsupporting
confidence: 70%
“…This coastal, nearshore habitat use, which has also been reported in previous studies (Francis et al, 2019), exposes this generally pelagic species to shore-based fisheries. While most individuals in this study were mature, previous studies on juveniles have also reported similar habitat use patterns between open-ocean and continental shelf use (Rogers et al, 2015;Vaudo et al, 2017;Byrne et al, 2019). Juveniles tagged off the Yucatan Peninsula demonstrated high residency to the eastern edge of the Campeche Bank (Vaudo et al, 2017;Byrne et al, 2019), and juveniles tagged off the coast of Australia exhibited high site fidelity to the mid-outer continental shelf near the Great Australian Bight (Rogers et al, 2015).…”
Section: Discussionsupporting
confidence: 66%
“…where m = month (1-12; Byrne et al, 2019). To account for individual variation, we included shark ID as a random effect.…”
Section: Behavioral Analysismentioning
confidence: 99%
“…With ongoing climate change impacting ecosystems worldwide, an urgent question is how the subtly different life history strategies of mobulids, carcharhinids and cheloniids buffer or intensify their demographic responses to climate change induced shifts in environmental stochasticity ( Table 1; Carr et al, 1978;Morreale et al, 1982;Limpus and Reed, 1985;Janzen, 1994;Hawkes et al, 2009;Moffitt et al, 2015;Marn et al, 2017a). This requires in depth understanding of their demographic responses to shifts in environmental autocorrelation and good environment frequency (Table 1), and the physiological processes that drive these (Marn et al, 2017b), which is all essential for the successful conservation management of marine megafauna (Cortés, 2002;Oh et al, 2017;Byrne et al, 2019).…”
Section: Stochastic Environmentmentioning
confidence: 99%